Numerical investigation of airflow field and CO2 distribution inside a seminar room for sensor placement. (December 2021) - Mou, Jianqiang; Cui, Shan; Khoo, David Wee Yang
Abstract: The measurement data quality of CO2 sensors plays a critical role in the implementation of the demand control ventilation (DCV) using a network of CO2 sensors. In this paper, the airflow field and spatial distribution of CO2 in an indoor space such as a seminar room was investigated utilizing computational fluid dynamics (CFD) analysis. The locations in the seminar room for proper placement of the CO2 sensors are identified, for assuring the measurement data quality and effective DCV to achieve high energy efficiency.